2019
DOI: 10.1111/aji.13098
|View full text |Cite
|
Sign up to set email alerts
|

The immunophenotype of decidual macrophages in acute atherosis

Abstract: Problem: Acute atherosis is a uteroplacental arterial lesion that is associated with pregnancy complications such as preeclampsia and preterm birth, the latter being the leading cause of perinatal morbidity and mortality worldwide. However, the immunobiology of acute atherosis is poorly understood. Method of study:Placental basal plate samples were collected from women who delivered with (n = 11) and without (n = 31) decidua basalis lesions of acute atherosis.Multicolor flow cytometry was used to quantify M1-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 129 publications
2
13
0
Order By: Relevance
“…Our recent immunohistochemical investigations confirmed that perivascular infiltrates were not consistently present or large around all acute atherosis lesions and that adaptive CD4 helper T cells may be involved, whereas the presence of Tregs (FOXP3þ) was almost absent, 73 again demonstrating similarities and discrepancies relative to early atherosclerosis lesions. 92 The recent findings of a more prevalent proinflammatory macrophage phenotype in the decidua basalis with acute atherosis and an intravascular monocyte source for macrophages in acute atherosis 93 support our hypothesis that both tissue-based and circulation-based cellular pathways lead to decidual acute atherosis. 18 Similarities among the circulating biomarkers also exist between acute atherosis and atherosclerosis.…”
Section: Expert Reviewsupporting
confidence: 69%
“…Our recent immunohistochemical investigations confirmed that perivascular infiltrates were not consistently present or large around all acute atherosis lesions and that adaptive CD4 helper T cells may be involved, whereas the presence of Tregs (FOXP3þ) was almost absent, 73 again demonstrating similarities and discrepancies relative to early atherosclerosis lesions. 92 The recent findings of a more prevalent proinflammatory macrophage phenotype in the decidua basalis with acute atherosis and an intravascular monocyte source for macrophages in acute atherosis 93 support our hypothesis that both tissue-based and circulation-based cellular pathways lead to decidual acute atherosis. 18 Similarities among the circulating biomarkers also exist between acute atherosis and atherosclerosis.…”
Section: Expert Reviewsupporting
confidence: 69%
“…To further explore the mechanisms whereby the loss of Tregs induces adverse perinatal outcomes, we explored the cellular repertoire at the maternal-fetal interface, in the placenta, and in the maternal circulation. This research question was based on previous studies showing that PTL involves stereotypical cellular responses at the maternal-fetal interface ( Arenas-Hernandez et al, 2016 , 2019 ; St Louis et al, 2016 ; Xu et al, 2016 ; Gomez-Lopez et al, 2017a ; Rinaldi et al, 2017 ; Garcia-Flores et al, 2018 ; Xu et al, 2018 ; Leng et al, 2019 ; Slutsky et al, 2019 ), in the placenta ( Salafia et al, 1991 ; Redline and Patterson, 1994 ; Kim et al, 2009 , 2015b ; Gill et al, 2019 ), and in the maternal circulation ( Gervasi et al, 2001 ; Pique-Regi et al, 2019 ). Foxp3 DTR dams underwent partial or total depletion of Tregs, and the decidua, myometrium, placenta, and peripheral blood were collected in preterm gestations.…”
Section: Resultsmentioning
confidence: 99%
“…Mox macrophages account for almost a third of the total macrophage content of advanced atherosclerotic plaques in mice [120,127] and play an antioxidant role dependent on their overexpression of Nrf2-related genes, such as heme oxygenase-1 ( HMOX-1 ), sulforedoxin-1 , and thioredoxin reductase [126,127,128]. Mox macrophages were initially described only in mouse models of atherosclerosis [127,129] but have since been identified in humans [130].…”
Section: Innate Immunitymentioning
confidence: 99%